Pengembangan Media Pembelajaran 3 Dimensi Interaktif Berbasis Web Pada Materi Perakitan Komputer Untuk Siswa Kelas X TKJ di SMK Negeri 1 Bantul - Nisma Fauziyah Istiqomah; Priyanto (Journal of Information Technology and Education (JITED), 2023)
This research aims to: (1) Develop web-based interactive 3-dimensional learning media products on computer assembly materials for class X students majoring in Computer Network Engineering at SMK Negeri 1 Bantul. (2) Determine the feasibility of web-based interactive 3-dimensional learning media in computer assembly material for class X students majoring in Computer Network Engineering at SMK Negeri 1 Bantul. The research is using the Research and Development (R&D) method. The research subjects were 71 students of class X Computer and Network Engineering at SMK Negeri 1 Bantul. The feasibility assessment of learning media was carried out by one material expert and one media expert, each of whom were computer assembly material teachers and expert lecturers. The instrument used in this research is a questionnaire. Data analysis technique using descriptive analysis techniques through percentage techniques. The results showed that: (1) web-based interactive 3-dimensional learning media on computer assembly material for class X TKJ SMK Negeri 1 Bantul can be well developed, (2) The feasibility test of material aspects by material experts obtained 83.8% results in the category "very feasible", the media aspect obtained 78.3% results with the "very feasible" category, and student testing (respondents) obtained 86.5% results with the "very feasible" category. This shows that web-based interactive 3-dimensional learning media is very feasible to use in learning computer assembly material.